1989
DOI: 10.1161/01.atv.9.4.511
|View full text |Cite
|
Sign up to set email alerts
|

A biologically plausible model of thickening of arterial intima under shear.

Abstract: A biologically plausible model of the early thickening of the arterial Intima has been developed to interpret experimental data relating hemodynamlc shear to human Intimal morphology. The model Included many processes known or commonly believed to take place In the vascular Intima, including: smooth muscle cell migration, proliferation, metabolism, and expression of extracellular matrix; llpoproteln kinetics and binding; and monocyte chemotaxls, conversion to macrophage, and foam cell formation. Certain of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Hypotheses explaining the localization of atherosclerotic lesions include hemodynamic stresses related to arterial geometry [1][2][3][4] ; anatomic, cellular, or biochemical variations in the arterial wall, particularly in endothelium 5 ; smooth muscle cell mutations leading to monoclonal proliferation 6 ; and infectious agents. 7 Most of the established major risk factors for coronary heart disease are associated with the extent of both fatty streaks and raised lesions in the large muscular and elastic arteries of adults 8 and also in arteries of adolescents and young adults.…”
mentioning
confidence: 99%
“…Hypotheses explaining the localization of atherosclerotic lesions include hemodynamic stresses related to arterial geometry [1][2][3][4] ; anatomic, cellular, or biochemical variations in the arterial wall, particularly in endothelium 5 ; smooth muscle cell mutations leading to monoclonal proliferation 6 ; and infectious agents. 7 Most of the established major risk factors for coronary heart disease are associated with the extent of both fatty streaks and raised lesions in the large muscular and elastic arteries of adults 8 and also in arteries of adolescents and young adults.…”
mentioning
confidence: 99%
“…SMC replication is well documented in these models, an extensive list of cell types has been postulated to provide the mitogenic signal, and based on these studies several theories of atherogenesis in humans have been advanced (5)(6)(7)(8)(9)(10). During the early stages of atherogenesis, macrophages that adhere and infiltrate vascular endothelium are good candidates for such growth factor production as platelet-derived growth factor (PDGF) and interleukin 1 (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…1,2,13,14 In our study, we found that B-flow sonography with high frame rates could visualize both the vascular hemodynamics and the interaction of blood flow with anatomical structures inside the vessel. In contrast, these fine details are often masked by the color overlay in color flow imaging.…”
Section: Discussionmentioning
confidence: 70%
“…6,14 Such hemodynamic characteristics tend to increase the residence time of circulating particles in susceptible regions and may result in shear stress-induced platelet aggregation, whereas particles are cleared rapidly from regions of relatively high wall shear stress and unidirectional laminar flow. 15,16 In addition, shear stress modulates the transcription of genes for nitric oxide synthase, platelet-derived growth factor A-and B-chain, prostacyclin, and transforming growth factor 1.…”
Section: Discussionmentioning
confidence: 99%